Scientific communication and the institutional repository within the PPGE/UFAM (Research, Society and Development, 2022)
The contribution of UFAM's institutional repository as a tool for knowledge production in the “education, cultures and Amazonian challenges” concentration area of the UFAM Graduate Program in Education. The research aims to analyze if self-archiving can contribute to the consolidation of the area of the aforementioned program, especially because it presents peculiarity in its thematic area. The theoretical-methodological path adopted is the cartography of Deleuze and Guattari (2011), seeking to know the movement of becoming and the singularities observed in walking, so it was necessary to know the UFAM guidelines procedures described on 1065/2017 and the area document of CAPES 2016, trying to find legal incentives for open access and repository feed. It was observed that the repository is not used in its effective potential by the program with the propose as a means of making its production visible and serving as a basis for the production of new knowledge about the concentration area, considering that the UFAM repository is part of the Northern Networking. Institutional Repositories and that would bring visibility of the program production at the regional level. Thus, it is necessary to adopt practices that contribute to the repository's self-archiving, consequently to consolidate the program's concentration area, it is mandatory that the document that CAPES area of education also accompanies the development of the free access and open culture movement that it will be innovator for new structures of scientific communication.